Studi Analisis Instrument Penilaian: Menguji Reliabilitas, Taraf Kesukaran, Daya Pembeda Secara Empirik dan Rasional - Ratna Sari; Julita Evawani; Zuhraini; Ansor (Yayasan Dharma Lentera Khatulistiwa (MALEWA), 2026)
In the world of education, of course, there is no escape from the assessment, to know the level of learning success that is conveyed to the students, before conducting an assessment, of course, it requires several analysis so that the assessment is not considered as a deviation anomaly. This research aims to analyze the assessment instruments used in the learning process to determine the level of eligibility, validity, and effectiveness in measuring the learning outcomes of learners. Assessment instruments are an important component in learning evaluation because they function to measure the achievement of competence objectively and systematically.The method used in this research is a descriptive approach by studying the form, content, and suitability of the instrument with learning indicators. The results of the analysis show that a good assessment instrument must meet the criteria that are valid, reliable, objective, and in accordance with the goals and learning indicators that have been set. Thus, the analysis of assessment instruments is very important to be carried out so that the assessment process can provide an accurate picture of the student's ability.